Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

The work of a student to solve the equation 3(2x − 4) = 8 + 2x + 6 is shown below: Step 1: 3(2x − 4) = 8 + 2x + 6 Step 2: 5x − 7 = 14 + 2x Step 3: 5x − 2x = 14 + 7 Step 4: 3x = 21 Step 5: x = 7 In which step did the student first make an error and what is the correct step? (5 points) Group of answer choices Step 3; 5x + 2x = 14 + 7 Step 3; 5x − 2x = 14 − 7 Step 2; 6x − 12 = 14 + 2x Step 2; 6x − 7 = 2(6 + x + 4)

Sagot :

The answer was actually posted on another one but it should be step 2; 6x - 12 = 14 + 2x. Or you can search the question again on here and you should find it!
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.